Species (biological, biochemical) features of the causative agent of bovine streptococcosis isolated on the territory of Kazakhstan - ALMIRA ILIMBAYEVA; NATALYA YEGOROVA; FLYURA BAKIYEVA; GULZIRA KYDYROVA; SALTANAT NUSSUPOVA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ilimbayeva A, Yegorova N, Bakiyeva F, Kydyrova G, Nussupova S. 2025. Species (biological, biochemical) features of the causative agent of bovine streptococcosis isolated on the territory of Kazakhstan. Biodiversitas 26: 1114-1123. The research was focused on identifying and characterizing streptococci responsible for mastitis in cattle, highlighting their pathogenic characteristics and antibiotic resistance. The goal was to develop more effective diagnostic, preventive, and treatment methods to reduce the impact of streptococcal infections on animal husbandry. Molecular techniques like Polymerase Chain Reaction (PCR) and DNA sequencing were used for precise species identification, while microbiological and biochemical analyses provided insights into their pathogenicity and resistance profiles. The identified streptococci included Streptococcus agalactiae, Streptococcus dysgalactiae, Streptococcus uberis, Streptococcus bovis complex, Streptococcus pyogenes, Streptococcus zooepidemicus, Streptococcus canis, and Streptococcus suis, and each species exhibited unique characteristics. For example, S. agalactiae showed beta-hemolytic activity, making it highly pathogenic to the mammary gland, while S. dysgalactiae demonstrated both alpha- and beta-hemolytic activity. S. uberis could thrive in high NaCl concentrations and showed notable enzymatic activity, and S. bovis complex exhibited gamma-hemolysis with the ability to grow in saline conditions. Additionally, beta-hemolytic species like S. pyogenes, S. zooepidemicus, S. canis, and S. suis highlighted their roles in respiratory diseases and interspecies transmission. The study underscores the importance of species-specific differentiation in streptococcal infections, as it is crucial for tailoring effective treatment and prevention strategies. This contributes to improved approaches in diagnosing, preventing, and treating mastitis in cattle, particularly in the context of increasing antibiotic resistance.